Rooting Response of Melada (Piper colubrinum) to Several Mixed Concentrations of IBA and NAA and Two Types of Commercial Root Stimulant - Hanum, Farida; Rasmani, Risma; Putri, Viza Yelisanti (Indonesian Operations Research Association (IORA), 2022)
This study aimed to study the best type of auxin on P.colubrinum rooting compared to commercial type stimulants and to study the effective and efficient mixed auxin concentration for P.colubrinum cuttings. The experiment was carried out at the Greenhouse of the Faculty of Agriculture, University of Lampung from May 2018 to December 2018. The experiment used a completely randomized design with 3 replications. The treatment applied mixed auxin (NAA and IBA) with a total concentration of both mixtures of 1500 ppm, 2000 ppm, 2500 ppm and also applied two types of commercial stimulants. The results of the 0.05 BNT test analysis can be concluded that the combined auxin NAA + IBA at a total concentration of 1500 ppm is an effective and efficient auxin compared to mixed auxin with a total concentration of 2500, 2000, two types of commercial auxin and also a control on the root formation of P. colubrinum cuttings. although the effect on the variable is different or higher, it is considered the same in the 0.05 BNT test. In mixed auxin with a total of 1500 ppm the average number of primary roots in the node is 12 strands, the average number of primary roots in the cross section of the stem is 9.2 strands, the average number of primary roots is 21.2 strands, the average length of primary roots 27 cm and the average root wet weight was 8.3 g